The Influence of an Enriched Sport Program on Children’s Sport Motivation in the School Context: The ESA PROGRAM - Gentile, Ambra (Front Psychol, 2020)
PURPOSE: Besides the evident positive effect on body development, physical activity has proven to boost executive functions, especially if the exercises are enriched with cognitive stimuli. Previous studies have shown that introducing challenging exercises in the physical activity routine can also enhance motivation. Therefore, enriching a physical education program with cognitively challenging exercises may also foster children’s motivation during physical education classes, where the motivation is high at the beginning of the school year and low at the end of it. Therefore, the purpose of this paper is to test if a sport program enriched by cognitive stimuli may improve kids’ motivation or take them out from a state of amotivation along the school year. METHODS: A sample of 342 school children (203 boys, 139 girls) took part in the study. Participants were asked to complete a battery of motivation and perceived social support questionnaires before and after they completed the ESA Program, a sport program enriched with cognitive stimuli. Moreover, parents of these children attended four seminars about the importance of supporting children for the practice of regular physical activity (PA). A control group consisting of children that attended the ordinary physical education school class was also included. RESULTS: A repeated measures MANOVA model showed that the ESA Program was able to improve children’s general motivation, in particular the intrinsic motivation. The program was not effective in social support, but, independently from the group, the family social support in sports activities decreased for females. CONCLUSION: Apart from cognitive improvement, the ESA Program can have beneficial effects on children’s sports motivation in physical education, but not on perceived social support.